Divergent Strain‐Release Amino‐Functionalization of [1.1.1]Propellane with Electrophilic Nitrogen‐Radicals. (26th February 2020) - Kim, Ji Hye; Ruffoni, Alessandro; Al‐Faiyz, Yasair S. S.; Sheikh, Nadeem S.; Leonori, Daniele
Abstract: Herein we report the development of a photocatalytic strategy for the divergent preparation of functionalized bicyclo[1.1.1]pentylamines. This approach exploits, for the first time, the ability of nitrogen‐radicals to undergo strain‐release reaction with [1.1.1]propellane. This reactivity is facilitated by the electrophilic nature of these open‐shell intermediates and the presence of strong polar effects in the transition‐state for C−N bond formation/ring‐opening. With the aid of a simple reductive quenching photoredox cycle, we have successfully harnessed this novel radical strain‐release amination as part of a multicomponent cascade compatible with several external trapping agents. Overall, this radical strategy enables the rapid construction of novel amino‐functionalized building blocks with potential application in medicinal chemistry programs as p ‐substituted aniline bioisosteres. Abstract : Elektrophile Stickstoffradikale ermöglichen eine effiziente Aminofunktionalisierung von [1.1.1]Propellan unter Freisetzung von Ringspannung. Diese radikalische Reaktion kann für die divergente Erzeugung von 3‐substituierten Bicyclo[1.1.1]pentylaminen, die starke Anilin‐Bioisostere sind, genutzt werden.